The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1186/1472-6874-11-48
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the pelvic organ prolapse without a physical examination; (a community based study)

Abstract: BackgroundPelvic organ prolapse (POP) is a silent disorder with a huge impact on women's quality of life. There is limited data from community-based studies conducted to determine the prevalence of POP as its assessment needs a pelvic examination. We aimed to develop a simple screening inventory for identification of pelvic organ prolapse and then evaluate its sensitivity and specificity.MethodsThis study had two phases. In the first phase in order to develop a simple inventory for assessment of POP, the Pelvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…POP and its complications make an impact on a considerable economic burden on the affected person. About 11% of the American women undergo surgery for POP or incontinence before the age of 79, with 29.2% of the women having a chance of requiring additional surgery [10].…”
Section: Introductionmentioning
confidence: 99%
“…POP and its complications make an impact on a considerable economic burden on the affected person. About 11% of the American women undergo surgery for POP or incontinence before the age of 79, with 29.2% of the women having a chance of requiring additional surgery [10].…”
Section: Introductionmentioning
confidence: 99%
“…Such gynaecological conditions can impact on sexual well-being of women [ 7 , 8 ] and subsequently psychological problems. Difficulties arise when studying gynaecological morbidities because of the sensitive and hidden nature of complaints regarding of the genital area [ 9 ]. In areas where access to health care is often limited, women usually have to live with the consequences of fistula or prolapse for the rest of their lives [ 3 ] which can be a challenge, both physically and emotionally, as the symptoms can disrupt the woman’s day-to-day life [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thurmond et al 21 have reported that there are structural changes in the prostate of older men in response to hypoxia. Tehrani et al 22 have compiled the screening of POP without a physical examination. Their questionnaire-based study examined urinary incontinence following laughing, sneezing or coughing, urinary urgency, feeling pain during defecation and feeling or seeing a bulge in the vagina.…”
Section: Discussionmentioning
confidence: 99%